Morphological characteristics and motor abilities of physically active and inactive female high-school students - Marijana Simić; Jovan Vuković; Saša Marković; Mila Vukadinović (University of Banja Luka, Faculty of physical education and sport, 2015)
On a sample of 72 girls from high school "Svetozar Miletic" from Novi Sad, age 18 ± 6 months divided into two groups: physically active (at least 30 minutes of daily physical activities of moderate intensity) and insufficiently physically active (below average) was performed a research of transversal character with intent to determine whether there are statistically significant differences in morphological characteristics and motor abilities. The study applied 13 variables, five morphological (body height, body weight, body mass index, body fat percentage, m muscle mass percentage) and 8 motorically (flamingo balance test, hand tapping, sit and reach, standing broad jump, from lying to sitting position for 30 seconds, bent arm hang, shuttle run 10x5 m and endurance shuttle run). Obtained results of multivariate analysis (MANOVA) indicate that there are statistically significant differences between the variables in morphological characteristics at level of p = .02 and motoric abilities at the level of p = .00, while univariate analysis (ANOVA) indicates, that in morphological characteristics there are only differences in the percentage of muscle mass, at the level of p = .006, while in motor abilities difference was determined in all variables.